2012
DOI: 10.3389/fimmu.2012.00048
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Proteins in Autoimmune and Inflammatory Diseases

Abstract: Over the past two decades, heat shock proteins (HSPs) have been implicated in inflammatory responses and autoimmunity. HSPs were originally believed to maintain protein quality control in the cytosol. However, they also exist extracellularly and appear to act as inflammatory factors. Recently, a growing body of evidence suggested that the other class of stress proteins such as, endoplasmic reticulum (ER) stress proteins, which originally act as protein quality control factors in the secretory pathway and are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 130 publications
(167 reference statements)
3
56
0
Order By: Relevance
“…Recently, more and more evidences indicate that GRP78 plays diverse roles beyond the ER (Quinones et al 2008;Morito & Nagata 2012). Studies have shown that GRP78 is expressed on the cell surface in many tissue types, and involved in transducing signals from ligands as disparate as activated α2-macroglobulin and antibodies (Gonzalez-Gronow et al 2009;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more evidences indicate that GRP78 plays diverse roles beyond the ER (Quinones et al 2008;Morito & Nagata 2012). Studies have shown that GRP78 is expressed on the cell surface in many tissue types, and involved in transducing signals from ligands as disparate as activated α2-macroglobulin and antibodies (Gonzalez-Gronow et al 2009;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chronic ER stress has been implicated in the pathology of a number of conditions like diabetes, traumatic brain injury, sepsis and neurodegenerative diseases (8-10). Therefore, studying the ER stress response in both an in vitro and in vivo context can help uncover and shed light on the pathology and development of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…ER function is affected by various factors called ER stress, such as heat shock, cytotoxic chemicals, hypoxia, and inflammation, which lead to the disturbance of Ca 2+ homoeostasis and accumulation of unfolded proteins in the ER lumen (Ma and Hendershot, 2001;Kaufman et al, 2002). In autoimmune and inflammatory diseases, the ER activates the unfolded protein response (UPR) signaling pathways by protein folding, lipid and sterol biosynthesis, and storing intracellular Ca 2+ (Morito and Nagata, 2012). A class of ER stress proteins like members from heat shock proteins (HSPs) family serve as molecular chaperones and are induced in response to ER stress and then involved in protein folding and assembly (Kaufman, 1999).…”
Section: Introductionmentioning
confidence: 99%